Nostalgic journeys : from the Orient Express to ocean liners = Zeitreisen : zwischen Orient-Express und Ozeandampfer - Bitterle, Stefan (teNeues Media GmbH & Co., 2022)
Off to the coast or to the mountains, to a neighboring country or to another continent? In bygone days, there was no such choice, because virtually everything was far away and inaccessible. It was not until the invention of the railroad that this changed. Fishing villages became sophisticated seaside resorts, remote mountain areas became destinations for hiking and skiing enthusiasts and inns became grand hotels. This book takes you back to exciting times, back when traveling meant discovering the world in a stylish and sometimes adventurous fashion. Ride the Orient Express to the Far East, cross the Atlantic on huge ocean liners, travel Route 66 through the United States and break the sound barrier aboard the Concorde. Bon Voyage!